A strategy for Lakes ecological restoration by integrated constructed wetlands, Case study: lake Qaroun, Egypt. Issue 1 (1st December 2022) - Mostafa, H; Attia, S; Feisal, Z
Abstract: Wetlands have a significant impact on healing degraded ecosystems and restoring environmental balance for their broad range of benefits. Lakes are considered a type of wetlands combining terrestrial and aquatic ecosystems, it is important to restore lakes wetlands to regain the ecological services provided by these systems, which might have been severely altered from human pressure, pollution and urban development. This paper investigates the concept of ecological restoration of Lake Qaroun wetlands proposing an ecological restoration strategy to enhance the current situation of site by using integrated constructed wetlands. The research conducts a literature review of wetlands restoration concept and the values of integrated constructed wetland as a restoration approach, besides showcasing several case studies of lake restoration plans than choosing two similar case studies with same the environmental challenges to determine the efficiency range of their restoration plans and their physical impact on site. Lake Qaroun previous development plans and the current situation were reviewed to determine the factors of success or failure. The proposed strategy of ecological restoration using integrated constructed wetlands combines an extensive management /monitoring program supported by governance inclusion and public participation, to be further implemented to achieve a better impact and a successful restoration process.